DESAIN PEMBELAJARAN DESCHOOLING SOSCIETY DAN RELEVANSINYA DENGAN KONSEP KAMPUS MERDEKA - ita nurmalasari; khoirun nisa' (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2020)
This research aims to uncover the design of deschooling society learning that was initiated by Ivan Illich and its relevance to the concept of an independent campus which became the Nadiem Makariem program. the concept of an independent or independent campus of learning, this is used to analyze primary ideas within the scope of the problem coupled with other relevant references, the approach in this research is a philosophical, historical factual approach used to study, understand and express related thoughts dischooling society and independent or independent learning campuses, while philosophical approaches are needed to examine, interpret, to be analyzed in depth to be associated with the two concepts above. The results of the study show that there is a intervention between deschooling society and the concept of an independent campus and produce learning designs that can be applied to educational institutions and tertiary institutions.